Temporal trends in cancer mortality attributable to high BMI in Asia: an age-period-cohort analysis based on GBD 1992–2021 - Huang, Minguang; Wang, Liejiong; Lou, Ying; Qiu, Zhaoqi; Yu, Shengjian; Xuan, Feng (Frontiers in Endocrinology, 2025)
BackgroundHigh body mass index (BMI) is a well-established modifiable risk factor for cancer. This study aims to assess temporal trends and contributing factors in cancer mortality attributable to high BMI in Asia from 1992 to 2021.MethodsData were obtained from the Global Burden of Disease (GBD) study. We analyzed mortality attributable to high BMI for total cancer and 11 specific subtypes across 34 Asian countries and five GBD regions from 1992 to 2021. Age-standardized mortality rates (ASMRs), average annual percentage change (AAPC), and age-period-cohort effects were calculated. Decomposition analysis quantified the contributions of aging, population growth, and epidemiological change to the changes in cancer deaths.ResultFrom 1992 to 2021, high BMI-related cancer deaths in Asia rose from 29,908 to 123,693, with ASMR increasing from 1.42 to 2.46 per 100,000 (AAPC: 1.92%, 95% CI: 1.85–1.98). South Asia experienced the most rapid ASMR growth (AAPC: 3.16%), while High-income Asia Pacific showed a decline after 1997. Sex-specific analyses revealed that colorectal, liver, and leukemia in males and colorectal, breast, and uterine cancers in females contributed most to ASMRs. Decomposition analysis indicated that the change in deaths was mainly driven by epidemiological change (118.20%), followed by population growth (115.54%) and aging (79.83%). Age-period-cohort analysis demonstrated rising mortality risks in successive birth cohorts, particularly in East and South Asia, while period and cohort effects declined in High-income Asia Pacific. Local drift analyses showed increasing mortality trends in older age groups across most regions.ConclusionThe burden of cancer ASMR attributable to high BMI in Asia has risen substantially over the past three decades. Substantial heterogeneity exists across regions, countries, sexes, and cancer types. Targeted prevention strategies and cancer control policies are urgently needed to address this rising public health challenge.